Підприємницький потенціал внутрішньо переміщених осіб: механізми залучення та використання - Панькова, О.В.; Шастун, А.Д.; Касперович, О.Ю. (Економічний вісник Донбасу, 2021)
Авторами проаналізовано інформаційно-аналітичне забезпечення підприємницької діяльності внутрішньо переміщених осіб (ВПО) в Україні; визначено основні проблеми та перешкоди підприємницької діяльності ВПО; запропоновано пріоритетні напрями збереження, підтримки та розвитку вітчизняного підприємницького потенціалу ВПО. Розкрито переваги недержавних джерел підтримки підприємницької діяльності ВПО та розвитку соціального підприємництва. Визначено інституційні, правові, фінансово-економічні механізми державної регуляторної політики розвитку малого та середнього підприємництва (МСП) в Україні щодо ВПО. Запропоновано стратегічні напрями становлення підприємницького потенціалу ВПО на потреби регіонального та місцевого розвитку. Авторами проанализировано имеющееся информационно-аналитическое обеспечение предпринимательской деятельности внутренне перемещенных лиц (ВПЛ) в Украине; выявлены основные проблемы и препятствия предпринимательской деятельности ВПЛ, предложены приоритетные направления поддержки и развития отечественного предпринимательского потенциала ВПЛ. Раскрыты преимущества негосударственных источников поддержки предпринимательской деятельности ВПЛ и развития социального предпринимательства. Определены институциональные, правовые, финансово-экономические механизмы государственной регуляторной политики развития малого и среднего предпринимательства в Украине для ВПЛ. Предложены стратегические направления становления предпринимательского потенциала ВПЛ для удовлетворения потребностей регионального и местного развития. The information and analytical support of the entrepreneurial activity of internally displaced persons (IDPs) is analyzed. There is a lack of statistical accounting of the number of actually relocated businesses, IDP entrepreneurs from the Crimea and Donbass. The needs and problems of these displaced persons do not have a quantitative and qualitative dimension. There is no information on the regional distribution of resettlement of IDP entrepreneurs. The main problems and obstacles of IDP entrepreneurship have been identified. They are limited opportunities for self-employment, rehabilitation, start-up and development of SMEs and micro-entrepreneurship of IDPs in places of relocation. The state does not compensate for the loss of the ability of IDP entrepreneurs to continue their business activities due to partial or complete destruction of fixed assets, lack of business support programs, inability to obtain loans for resumption of activities and limited access to financial resources, etc. The priority directions of preservation, support and development of entrepreneurial potential of IDPs are offered, which are directed on maintenance of social justice concerning realization of the rights, freedoms and guarantees of IDP-entrepreneurs; creation of favorable institutional, legal, financial and economic, information and communication conditions for the restoration and development of IDP business; providing ample opportunities for IDP entrepreneurs to obtain loans and fixed assets, etc. The advantages of non-state sources of support for IDPs' business activities are revealed. These are international lending instruments: investment financing, reorientation of existing projects; international grant funding; international technical assistance. It has been proven that social entrepreneurship is an effective option for using the entrepreneurial potential of IDPs. The institutional, legal, financial and economic mechanisms of the state regulatory policy for the development of SMEs in Ukraine regarding IDPs have been identified. The need to establish partnership and coordination networks between the public, public and private sectors is noted. Strategic directions of formation of entrepreneurial potential of IDPs for regional and local development are offered.